Heterogenetic parabiosis between healthy and dystrophic mice improve the histopathology in muscular dystrophy - Lu, Aiping (Sci Rep, 2020)
Duchenne muscular dystrophy (DMD) is a progressive muscle disease, characterized by mutations in the X-linked dystrophin, that has several therapeutic options but no curative treatment. Transplantation of muscle progenitor cells for treatment of DMD has been widely investigated; however, its application is hindered by limited cell survival due to the harmful dystrophic microenvironment. An alternative approach to utilize progenitor cells and circulatory factors and to improve the dystrophic muscle pathology and microenvironment is through parabiotic pairing, where mice are surgically sutured to create a joint circulatory system. Parabiotic mice were generated by surgically joining wild type (WT) mice expressing green fluorescent protein (GFP) with mdx mice. These mice developed a common circulation (approximately 50% green cells in the blood of mdx mice) 2-weeks after parabiotic pairing. We observed significantly improved dystrophic muscle pathology, including decreased inflammation, necrotic fibers and fibrosis in heterogenetic parabionts. Importantly, the GFP + cells isolated from the mdx mice (paired with GFP mice) underwent myogenic differentiation in vitro and expressed markers of mesenchymal stem cells and macrophages, which may potentially be involved in the improvement of dystrophic muscle pathology. These observations suggest that changing the dystrophic microenvironment can be a new approach to treat DMD.